Intimate partner sexual violence and early resumption of sexual intercourse among married postpartum women in Ethiopia: a survival analysis using Performance Monitoring for Action data - Abeje, Eyob Tilahun; Bayou, Fekade Demeke; Getaneh, Fekadeselassie Belege; Asmare, Lakew; Endawkie, Abel; Gedefie, Alemu; Muche, Amare; Mohammed, Anissa; Ayres, Aznamariam; Melak, Dagnachew (Frontiers in Global Women's Health, 2025)
IntroductionMany women worldwide resume sexual intercourse soon after childbirth, often before the recommended six-week recovery period. Early postpartum intercourse poses health risks, including infections and delayed healing. This study aims to assess the timing of resuming sexual intercourse and its predictors among postpartum women in Ethiopia using PMA data.MethodsThe data was from the Performance Monitoring for Action (PMA) project, a cross-sectional design followed by cohort follow-up, employed to analyze the sociodemographic and reproductive characteristics of women aged 15–49. Pregnant women and those up to nine weeks postpartum at baseline were included in the study. Descriptive statistics and Cox proportional hazard model were used for analysis using R 4.4.1 software. Proportional hazard assumption was assessed using graphical and statistical tests. The model fitness was checked using martingale residual plot.ResultsThe study found that 29% of participants resumed sexual intercourse before the recommended 42 days postpartum, while 91% resumed by 68 days. The median survival time was 8 weeks (57 days). The hazard of early sexual resumption was 5.56 times higher among women who experienced intimate partner violence compared to those who did not.DiscussionEarly sexual resumption among postpartum women in Ethiopia was high. Intimate Partner violence was a significant predictor of early sexual resumption. It is better to promote IPV prevention and postpartum couple counseling to support safe and consensual sexual resumption.